2014
DOI: 10.1002/rcm.6897
|View full text |Cite
|
Sign up to set email alerts
|

The mobility of nitrogen across tree‐rings of Norway spruce (Picea abies L.) and the effect of extraction method on tree‐ring δ15N and δ13C values

Abstract: Our results indicate that the extraction of mobile N compounds through the rapid extraction procedure is not necessary prior to the determination of Norway spruce δ(15)N or δ(13)C values in dendrochemical studies. δ(15)N values, however, must be interpreted with great care, particularly when used as a proxy for the N status of trees, due to the very high mobility of N within the tree stem sapwood of Norway spruce over several decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(125 reference statements)
0
15
0
Order By: Relevance
“…Five trees (ten cores) from each site were selected for C and N tree-ring isotope analyses. Based on the findings of Tomlinson et al (2014), where no significant changes in isotopic composition of either C or N were found after the extraction of mobile compounds, we decided to use whole wood material. Single tree-rings were separated with a razor blade under a microscope, and then pooled for each individual tree-ring year per site.…”
Section: Sample Preparation and Isotope Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Five trees (ten cores) from each site were selected for C and N tree-ring isotope analyses. Based on the findings of Tomlinson et al (2014), where no significant changes in isotopic composition of either C or N were found after the extraction of mobile compounds, we decided to use whole wood material. Single tree-rings were separated with a razor blade under a microscope, and then pooled for each individual tree-ring year per site.…”
Section: Sample Preparation and Isotope Analysesmentioning
confidence: 99%
“…However, there are few studies that investigate tree-ring d 15 N. This may be because N concentrations in tree-rings are low (relative to C in tree-rings and N in foliage) and related methodological difficulties (Savard 2010). Low tree-ring N concentrations also result in the movement of mobile N compounds between tree-rings (Tomlinson et al 2014). These N recycling processes within the tree play an important role in meeting the N demand from sinks within, potentially masking N deposition signals and the impact of added N on tree-ring d 15 N values (Evans 2001;Kolb and Evans 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wood is often difficult to analyze because of its high C/N ratio (Savard et al, 2020), meaning that its combustion for mass spectrometry produces much CO 2 but little N. Wood must be finely ground before analysis because the combustion of even tiny wood chips is not fast enough. In some species, it has been observed that tracer N also enters older wood (Tomlinson et al, 2014). It is thus important to take wood cores that go deep enough into the trunks.…”
Section: Treesmentioning
confidence: 99%
“…Coarse roots (> 2 mm), stem, and leaf samples were taken on May 20 (shoot growth stage), August 2 (green leaf stage), October 19 (pre-abscission stage), and November 29 (post-abscission stage), with fresh litter collected from litter traps (size: 1 m 2 ). Sapwood was sampled by using an increment borer (10 mm) and not heartwood, assuming that there was no variation in N content in heartwood throughout the growing season [26]. Leaf samples were taken from the lower canopy from different leaf clusters.…”
Section: Sample Collection and Treatmentsmentioning
confidence: 99%